Improving flame retardancy and melt processability of polyethersulfone using low molecular weight additives. Issue 24 (7th March 2016) - Owusu‐Nkwantabisah, Silas; Staudt, Claudia; Lesser, Alan J.
ABSTRACT: The effect of a calcium stearate (CaSt2 ) additive on the melt processability and flame retardancy of polyethersulfone (PES) was studied. Measurements of the viscosity of PES and its composites showed a marked decrease in viscosity with increase in the fraction of CaSt2 additive. About 40% reduction in viscosity of PES was achieved with addition of 5 wt % CaSt2 . By decreasing the viscosity, the CaSt2 additive enabled the melt extrusion of PES at lower temperatures up to 90 °C below that of conventional melt processing. The flammability was also investigated using a Pyrolysis Combustion Flow Calorimeter (PCFC). The CaSt2 additive resulted in tremendous improvement in the flame retardancy of PES as evident in the reduction of the heat release capacity (HRC) of the composites by up to 37%. Moreover, the peak of heat release rate (pHRR) of PES in the composites was up to 84% lower than in the neat polymer. The remarkable improvement in flame retardancy of PES was demonstrated to be related to the rapid charring of the composites and the in situ formation of calcium carbonate/calcium oxide upon decomposition of CaSt2 . The CaSt2 additive was also found to enhance the flame retardancy of thermoplastics including polyamide‐6 and polypropylene (PP). © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43525. Abstract :